Hybrid PET-optical imaging using targeted probes - Nahrendorf, Matthias (National Academy of Sciences, 2010)
Fusion imaging of radionuclide-based molecular (PET) and structural data [x-ray computed tomography (CT)] has been firmly established. Here we show that optical measurements [fluorescence-mediated tomography (FMT)] show exquisite congruence to radionuclide measurements and that information can be seamlessly integrated and visualized. Using biocompatible nanoparticles as a generic platform (containing a (18)F isotope and a far red fluorochrome), we show good correlations between FMT and PET in probe concentration (r(2) > 0.99) and spatial signal distribution (r(2) > 0.85). Using a mouse model of cancer and different imaging probes to measure tumoral proteases, macrophage content and integrin expression simultaneously, we demonstrate the distinct tumoral locations of probes in multiple channels in vivo. The findings also suggest that FMT can serve as a surrogate modality for the screening and development of radionuclide-based imaging agents.